Hippolyta's view some Christian aspects of Shakespeare's plays. - Bryant, J. A. (Joseph Allen), 1919-1999 (University of Kentucky Press, 1961)
Scholars have already demonstrated that Shakespeare 's language abounds in Biblical allusions and references, but Mr. Bryant now undertakes to show us how such details may bear on the full meaning of the plays. Seeking to interpret Shakespeare's plays as Christian poetry, Mr. Bryant has developed in this significant work a new critical approach which may have far-reaching consequences for future Shakespearean scholarship. In an introductory essay the author shows that the typological view of Scripture was a familiar one to the Christians of Shakespeare 's time; he suggests that for Shakespeare,